'You feel like you're an artist. Like Leonardo da Vinci': Capturing young children's voices and attitudes towards visual arts. (1st September 2017) - Tan, Michelle; Gibson, Robyn
Early childhood research is focusing increasingly on issues of acknowledging and respecting the 'voices' of young children. Much of the focus in arts education research, however, has explored adult attitudes, resulting in what seems the invisibility of young children's opinions. Conducted in the context of early childhood education in Australia, the study, following a phenomenological approach, sought to understand the place of visual arts in the lives of four young children aged five to six years in a combined Kindergarten/Year One classroom located in Sydney. A range of childsensitive research tools were adapted from the 'Mosaic approach' to explore how children understand and conceive their early experiences of visual arts learning. In acknowledging the views of children, possibilities for improving arts pedagogy were considered as new questions emerged. The study confirmed the need to acknowledge and validate children's rich and perceptive attitudes through meaningful experiences and valued conversations.